Italian Futurism in Russian poetry: Vladimir Mayakovsky’s poetic revolution - New, K (Center for Promoting Ideas, 2020)
The aim of the present article is to analyse the reception of the poetic principles of Italian Futurism in the works of the most famous Russian Futurist poet, Vladimir Mayakovsky. The author of the article tracesthe change of hisartistic views and its impact on the development of his self-representation. Mayakovsky’s poetic self-identification divides into two stages, which are influenced by personal, social and political factors of his time. In his pre-revolutionary works, the poet’s self-identity is marked by intense loneliness and despondency arising from his protest against the bourgeois and the dreariness of mundane life. Mayakovsky’s early poetry follows the programmes formulated by Italian and Russian Futurists, such as the demolition of traditional art, revolt against poetic canons, disrespect for acknowledged masters of lyrical verse (primarily Pushkin), denial of the established semantics of lexical units, destruction of poetic vocabulary, disassociation of metaphors. During the second stage of his development as a poet, Mayakovsky represents himself through a persona engrossed in the interests of the post-revolutionary community and the new state: the feeling of loneliness is ousted by the sense of solidarity with the nation creating a new civilization; despondency gives way to the feeling of self-fulfillment. Mayakovsky’s new self-identity as a revolutionary corresponds to his revolutionary changes of both the semantics and the structure of Russian verse: heintroduces original themes into poetry (praising the revolution, glorifying the new socialist order); he pioneers the art of poetic propaganda, relating verbal art to the acts of sanitation and physical toil. In the poems belonging to the second period, Mayakovsky gradually departs from the canons of Futurism, shows admiration for Pushkin and seeks to establish an intertextual poetic dialogue with the most renowned of the Russian poets.